Natural Questions: A Benchmark for Question Answering Research - Kwiatkowski, Tom; Palomaki, Jennimaria; Redfield, Olivia; Collins, Michael; Parikh, Ankur; Alberti, Chris; Epstein, Danielle; Polosukhin, Illia; Devlin, Jacob; Lee, Kenton; Toutanova, Kristina; Jones, Llion; et al. (Transactions of the Association for Computational Linguistics, 2019)
We present the Natural Questions corpus, a question answering data set. Questions consist of real anonymized, aggregated queries issued to the Google search engine. An annotator is presented with a question along with a Wikipedia page from the top 5 search results, and annotates a long answer (typically a paragraph) and a short answer (one or more entities) if present on the page, or marks null if no long/short answer is present. The public release consists of 307,373 training examples with single annotations; 7,830 examples with 5-way annotations for development data; and a further 7,842 examples with 5-way annotated sequestered as test data. We present experiments validating quality of the data. We also describe analysis of 25-way annotations on 302 examples, giving insights into human variability on the annotation task. We introduce robust metrics for the purposes of evaluating question answering systems; demonstrate high human upper bounds on these metrics; and establish baseline results using competitive methods drawn from related literature.